Ethical implications of preclinical studies - I. N. Tyurenkov; E. M. Lomkina; D. V. Kurkin; D. A. Bakulin; E. V. Volotova (Регуляторные исследования и экспертиза лекарственных средств)
Animal experiments are fundamental for the biomedical science. The development of new drugs is always associated with a large number of preclinical experiments in animals. Experimental data make it possible to predict the drug efficacy and safety in humans. There are more than 100 million laboratory animals that are used by researchers every year worldwide. This fact raises a number of concerns regarding the legality and ethical appropriateness of using such a large number of animals. This article discusses the problem of using an unreasonably large number of experimental animals during preclinical drug studies, as well as potential ways of streamlining existing methods used for determining the acute and subacute toxicity of drugs in order to minimize the time of the study and the number of animals used. In addition, we review the problem of systematizing experimental data and potential ways of their standardization in line with the European legislation regulating ethically approved use of animals in experiments.